The Link between Physical Fitness and Learning Outcomes of Physical Education, Sports and Health of Students at SMA Negeri Unggul Dharmasraya - Regi Saputra; Muhammad Sukron; Dian Estu Prasetiyo (The Future of Education Journal, 2023)
The Relationship between Physical Fitness and Learning Outcomes at Unggul Darmasraya State Senior High School, Thesis. Physical fitness is a person's ability to easily carry out daily activities without feeling excessively tired and still have energy reserves to carry out other activities. Through good physical fitness, it is certain that students will be able to accept and absorb the lessons given by the teacher so that the goal of creating the next generation that excels in all aspects can be realized. The data from the test results are processed using a computerized SPSS system. The results showed: 1) The level of physical fitness of class Xe4 students at Unggul Darmasraya State Senior High School was in the moderate category. 2) Class Xe4 Student Learning Outcomes of Unggul Darmasraya State Senior High School are in the Good Category. 3) There is a significant positive relationship between the level of physical fitness and the learning outcomes of Class Xe4 SMA Negeri Unggul Darmasraya in 2023. The population in this study were Class Xe4 students at Unggul Dharmasraya High School who were registered in the odd semester (1) of the 2022/2023 academic year, consisting of 1 class with a total of 25 people. Sampling uses a purposive sampling technique, namely samples taken according to the purpose or desire, so that a sample class is obtained, namely class Xe4 (2) male and female, totaling 25 people. Data Analysis Techniques Using Product Moment Correlation Analysis.